2017
DOI: 10.1016/j.jid.2016.06.634
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immunity in Fibrosarcomatous Dermatofibrosarcoma Protuberans and Response to Imatinib Treatment

Abstract: Dermatofibrosarcoma protuberans (DFSP), although rare, is the most frequent skin sarcoma. Here, we focus on DFSP carrying the fibrosarcomatous transformation (FS-DFSP). FS-DFSP responds to imatinib (IM); however, tumor relapse often occurs. In a series of 21 pre- and post-treatment FS-DFSP samples, the present study explored the events that occur at the tumor site during IM therapy. Gene expression profile and immunohistochemistry analyses documented the occurrence of IM-induced senescence phenotype in the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 34 publications
0
29
0
4
Order By: Relevance
“…Moreover, it has been observed that imatinib treatment causes immunological changes both in tumor cells and the surrounding tissue . These changes suggest that a combined or sequential treatment regimen consisting of imatinib and immunotherapy may be a possible option .…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, it has been observed that imatinib treatment causes immunological changes both in tumor cells and the surrounding tissue . These changes suggest that a combined or sequential treatment regimen consisting of imatinib and immunotherapy may be a possible option .…”
Section: Treatmentmentioning
confidence: 99%
“…Imatinib acts as a multikinase inhibitor in the PDGFRB signaling pathway, which is dysregulated by the t(17;22) translocation frequently seen in DFSP, resulting in the fusion of PDGFRB to the COL1A1 gene . Imatinib also seems to modulate the adaptive immune response to DFSP, thus paving the way for novel therapeutic approaches such as innovative combination immunotherapies . Given the good response rates, especially in a neoadjuvant setting, imatinib is given preference over radiation therapy in English‐speaking countries.…”
Section: Dermatofibrosarcoma Protuberansmentioning
confidence: 99%
“…Imatinib greift als Multikinaseinhibitor in den PDGFRB-Signalweg ein, der durch die häufi g in DFSP vorkommende t(17;22)-Translokation mit Fusion des PDGFRB mit dem Gen für COL1A1 dysreguliert ist [ 6 ] . Imatinib scheint zudem die adaptive Immunantwort gegen DFSP zu modulieren und so Ansätze für innovative immuntherapeutische Kombinationstherapien zu eröffnen [ 7 ] . Bei guten Ansprechraten, vor allem im neoadjuvanten Bereich, wird der Therapie mit Imatinib im angloamerikanischen Sprachraum der Vorzug vor einer Radiatio gegeben.…”
Section: Introductionunclassified
“…Des Weiteren wurde beobachtet, dass eine Therapie mit Imatinib immunologische Veränderungen in Tumorzellen und deren Umgebungsgewebe hervorruft . Diese Veränderungen weisen auf die Möglichkeit einer Kombinations‐ oder Sequenztherapie aus Imatinib und Immuntherapie hin .…”
Section: Therapieunclassified